VEKTORLAR JÁRDEMINDE ALGEBRALÍQ MÁSELELERDI ShEShIWDIŃ NÁTIYJELI USÍLLARÍ - Kalekeeva, T.T.; Maxsutova, U.D.; Quanıshbaeva, H.S. (SCIENCE and SOCIETY, 2025)
This article explores the interrelation between geometry and algebra through the use of vectors. It presents visual and intuitive methods for solving equations and inequalities based on the scalar product of vectors and its properties. The importance of integrating geometric and algebraic definitions of vectors in the teaching process is highlighted. A methodological approach is demonstrated through several practical problems and their solutions.